الترجمة والعولمة: إعادة تعريف دور المترجم كبابلي جديد في القرية الكونية (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
This piece of research attempts to redefine the role of the translator as neo-babelianist in this fast growing and changing global village. Since the ancient tale of the demolition of the Tower of Babel and its allegedly ominous consequences on humanity at large, up to the contemporary twenty first century with its complex technology, communications and marketing, translation has always proved to possess a teleological mission. If the modern global man claims that the Earth is his vast and accessiblt market, then it is translation that facilitates the communication among miscellaneous worldwide cultures. Irrespective of the depth of complexity of conflicting interests of the modern man globally, translators constantly prove their ability to handle new global terms and neologicams. They also respond genuinely to the demands of ideological stands, cope with the international conferences and simultaneous interpreting, and contribute through sustaining the philanthropic inspirational role of translation. The world current tendency toward more marketing and less human has never weakened the image of the ever existing astute translator. In brief, this research does not probe globalization as a pure concept per se, rather, it debates and scrutinises the intimate influential relationship between globalization and translation. يحاول هذا البحث إعادة تعريف دور المترجم كبابلي جديد في هذه القرية الكونية المتنامية والمتغيّرة على نحوٍ سريعٍ. فمنذُ انهيار برج بابل وإدّعاءات عواقبه الخطيرة على البشرية جمعاء—كما تروي القّصة القديمة—وصولاً إلى القرن الواحد والعشرين المعاصر بما ينطوي عليه من تكنولوجيا معقّدة واتّصالات وتسويق، برهنت الترجمة على امتلاكها لرسالةٍ هادفةٍ. فإذا ما ادّعى الإنسان الكوني الحديث أنّ الأرض بمنزلة سوقٍ واسعٍ سهل المنال، فإنّ التّرجمة هي مَن يسهّل التواصل بين ثقافات العالم المتنوّعة. وبغضّ النّظر عن عمق تعقيدات المصالح المتضاربة للإنسان الحديث على المستوى الكوني، فقد برهن المترجمون، وعلى الدّوام، قدرتهم على التّعامل مع المصطلحات والتعابير الكونية الجديدة. كما استجابوا حقيقةً لمتطلّبات المواقف الإيديولوجية، وواكبوا المؤتمرات العالمية والترجمة الفورية، وأسهموا من خلال دعمهم للدّور الخيّر والملهِم للتّرجمة. فالتوجّه الحالي للعالم نحو مزيدٍ من التّسويق وتقليلٍ من دور الإنسان لم يضعفِ البتّة صورة المترجم المتفهّم والمتواجد باستمرارٍ. باختصارٍ، إن هذا البحث لا يسبر أغوار العولمة كمفهومٍ بحتٍ بحدِّ ذاته، بل يناقش ويتفحّص العلاقة المؤثِّرة والحميمة بين العولمة والترجمة.